Socio-Economic Risk of Oil Pipeline Vandalism in Nigeria and its Remedy Using Satellite Constellations: An Evidence From Bayesian Spatial Modeling - Ogujiofor, G., O; Samuel, O, P; Ogujiofor B, D (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The threat posed by the vandalism of oil pipelines in Nigeria has resulted in a lack of petroleum products for consumers, loss of life, and significant damage to both property and valuable resources due to resulting fires. This situation has also led to the pollution of marine life and has contributed to food shortages. Nigerian government loses about twenty (20) billions of dollars of the activities of pipeline vandals. This exclude the monetary cost of loss of lives, property and the environmental resources. A spatial statistic based on Bayesian principles aids in measuring spatial patterns and offers understanding into the mechanism behind their formation. With advancements in technology, particularly in storage capacity, the acquisition of georeferenced data is prevalent in current domain sets. The Bayesian approach is commonly employed to analyze such datasets and discern spatial patterns. Although the pipeline vandalization is spatially heterogeneous in Nigeria, current regional estimates of this barbaric act hide the epidemic’s heterogeneity. A thorough examination of the prevalence of pipeline vandalism using district-level data could assist to developing the prevention strategies. The major aim of this research among others is to examine the spatial clustering of pipeline vandalism in Niger Delta region and assess the effects on the economy of Nigeria. This research proposes a cost-effective technique for resolving the challenge of oil pipeline vandalism using Earth observation systems (small Satellites/CubeSats) in the Low Earth Orbit and statistically monitoring the imagery data via the help of ArcGIS 10.4 software. The result from the ADSACBOPSS (Affordable DSA-CubeSat Based Oil Pipeline Surveillance System) show a high instant technique of preventing petroleum pipeline vandalization using Data obtained from Nigerian National Petroleum Cooperation (NNPC) and GRID3 open sources. The constellation of these Satellites/CubeSats, has short development time and can provide 24/7 real-time surveillance data throughout its lifetime. The ADSACBOPSS technique is readily available and I recommend that NNPC and Nigerian government in general should buy the idea and invest in the project to effectively stop petroleum pipeline vandalization. Bayesian hierarchical spatial modeling techniques were utilized to tackle the research goals. We noticed a favorable spatial connection in the geopolitical zones and state indicators during the spatial analysis. The application of the Getis–Ord statistic pinpointed three states—Ondo, Delta, and Rivers—as areas with heightened activity, while the South-South and South-West zones were identified as hotspots, with confidence levels of 95% and 90%, respectively, regarding the prevalence of pipeline vandalism.